Coordination models and languages : 22nd IFIP WG 6. 1 International Conference, COORDINATION 2020, held as part of the 15th International Federated Conference on Distributed Computing Techniques, DisCoTec 2020, Valletta, Malta, June 15-19, 2020, Proceedings /: 22nd IFIP WG 6. 1 International Conference, COORDINATION 2020, held as part of the 15th International Federated Conference on Distributed Computing Techniques, DisCoTec 2020, Valletta, Malta, June 15-19, 2020, Proceedings. (2020) - Unknown
No abstract available